Analysis of upper atmospheric effects on material per onboard atomic oxygen monitor system of SLATS - Kimoto, Yugo; Tsuchiya, Yuta; Miyazaki, Eiji; Goto, Aki; Yukumatsu, Kazuki; Imamura, Shunsuke (Frontiers in Space Technologies, 2022)
JAXA has proposed an innovative idea for satellites in Low Earth Orbit (LEO). The Super-Low Altitude Test Satellite (SLATS), also known as TSUBAME, is the first Earth observation satellite to occupy a Super-Low Orbit (S-LEO) or Very Low Earth Orbit (VLEO), below 300 km. The purposes of SLATS are (1) testing the maintenance of the satellite’s altitude with its ion engine against high atmospheric drag at a super-low altitude, (2) acquiring data on atmospheric density and atomic oxygen (AO), and (3) testing optical Earth observation. SLATS was successfully launched on December 23, 2017. SLATS was then altitude-controlled for 636 days to 271.7 km using chemical thrusters, aerodynamic drag, and ion engine propulsion. SLATS finally maintained its orbit of 167.4 km for seven days and finished its operation on October 1, 2019. All the SLATS and Atomic oxygen MOnitor (AMO) data was acquired during these operations. The AMO is one of the mission sensors that monitor AO and its effects on spacecraft materials. The data from the AMO contributes to the choice of materials in future S-LEO satellite design. The data obtained by the AMO are valuable in that they provide considerable knowledge on AO fluence and its effects on space materials.